PENYULUHAN KADAR CRP (C-REACTIVE PROTEIN) PADA PENDERITA TUBERKULOSIS DI KECAMATAN CILAWU SEBAGAI PENANDA ADANYA INFLAMASI - Nurisani, Astari; Mamay, Mamay; Mutmaina, Gina Nafsa; Sugiah, Sugiah; Pratama, Wisnu Arya (Ekalaya: Jurnal Pengabdian Kepada Masyarakat Indonesia, 2023)
Infection due to tuberculosis bacteria will cause inflammation in the body which will stimulate the emergence of C-Reactive Protein as a biomarker of inflammation. C-Reactive Protein (CRP) is a polypeptide molecule of the pentraxin group which is produced in the liver and controlled by cytokines especially Interleukin-6 (IL-6). CRP is useful for monitoring disease progression. CRP concentration is related to disease severity, infection and treatment effect. The purpose of this community service is to see CRP (C-Reactive Protein) levels in tuberculosis sufferers in the Cilawu sub-district and provide an understanding of CRP examination. The method used is counseling with LCD and examination of CRP levels in tuberculosis patients. The sufferers are collected in a house that has been mutually agreed upon. The results of the activity were that most of those present had CRP examination results on the 30 samples that had been examined, 24 people (80%) had positive results, and 6 people (20%) had negative results. CRP levels in positive tuberculosis patients obtained various results between 6 mg/L to 192 mg/L. Conclusion: the results of this community service illustrate that there is an inflammatory response of CRP to tuberculosis bacterial infection. After carrying out counseling and examining CRP levels, the community, especially tuberculosis sufferers, became aware and interested in carrying out CRP examinations as a form of monitoring the level of infection they were suffering from